2015
DOI: 10.1136/bmj.g7371
|View full text |Cite|
|
Sign up to set email alerts
|

Blood glucose concentration and risk of pancreatic cancer: systematic review and dose-response meta-analysis

Abstract: Objective To evaluate potential linear and non-linear dose-response relations between blood glucose and risk of pancreatic cancer.Design Systematic review and dose-response meta-analysis of prospective observational studies.Data sources Search of PubMed, Scopus, and related reviews before 30 November 2013 without language restriction.Eligibility criteria Prospective studies evaluating the association between blood glucose concentration and pancreatic cancer. Retrospective and cross sectional studies excluded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(100 citation statements)
references
References 42 publications
6
91
0
Order By: Relevance
“…Evidence has suggested that high glucose and type 2 diabetes might be risk factors for PC [35]. In our study, we also noted that blood glucose concentrations in PC groups were higher than control groups.…”
Section: Discussionsupporting
confidence: 52%
“…Evidence has suggested that high glucose and type 2 diabetes might be risk factors for PC [35]. In our study, we also noted that blood glucose concentrations in PC groups were higher than control groups.…”
Section: Discussionsupporting
confidence: 52%
“…This hypothesis was supported by a meta-analysis demonstrating a linear increase of 14% in pancreatic cancer risk with every 0.56mmol/L increase in fasting blood glucose levels. 24 Because of the high incidence of diabetes mellitus in the general population and the lack of a low-risk and low-cost PDA screening test, conducting mass PDA screening in all patients with new-onset diabetes mellitus is not feasible. Nevertheless, targeted screening for PDA (e.g., using endoscopic ultrasound [EUS]) may be feasible if diabetic individuals at the highest risk for PDA-associated diabetes could be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Due to one of the functions of the pancreas in regulating glucose metabolism, diabetes is a common presenting finding for pancreatic cancer. In one dose-response metaanalysis of prospective observational studies, it was shown that every 0.56 mmol/L increase in fasting blood glucose is associated with a 14% increase in the rate of pancreatic cancer [54]. This roughly translates to around a 0.35% change in the Hemoglobin A1C (HgbA1C).…”
Section: Other Risk Factors For Pancreatic Cancer Developmentmentioning
confidence: 99%